Penalaran moral pada siswa SLTP umum dan Madrasah Tsanawiyah - Zidni Immawan Muslimin (HUMANITAS: Indonesian Psychological Journal, 2004)
The purpose of this study is to find out the differences of moral reasoning between students of Sekolah Lanjutan Tingkat Pertama Negeri (SLTPN) and students of Madrasah Tsanawiyah Negeri (MTs N).The total subjects of the research were 53 students. The students of SLTPN "X" consisted 28 students and the students of MTs N consisted 25 students. All of subjects have above average (grade ll) intelligence level. The subjects were selected using purposive sampling technique. This research data collected using the Kohlberg Scale and Standard Progressive Matrices (SPM).Schefe test was applied to analyzed the data, which resulted that there is a difference of moral reasoning among the students of SLTP N "X" and MTs N "Y" (t:0,2248; p< 0,05) SLTP N average 2,420 and MTs N Naverage 2,660.